On the road (Scenario® - Il Nursing nella sopravvivenza, 2024)
Recently the FNOPI convened the council of scientific societies to 'chart the course' for the near future of nursing. Great changes await us, we are maturing a more specific professional culture, in which we rightly recognise colleagues who are experts in particular fields, we are becoming a community that talks and compares about evidence and good practice.But are we sure we are ready for a new leap? I was struck by the remark of a communications expert who gave me, clearly at my express request, an image of us as a divided and quarrelsome profession, ready to follow particular interests without, often, even considering the overall horizon. It was not easy to be told like that, but I must admit that in some respects it is profoundly true. [...]